Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2003
DOI: 10.1074/jbc.m307481200
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of the Sequential Processing of Semliki Forest Virus Replicase Polyprotein

Abstract: The replication of most positive-strand RNA viruses and retroviruses is regulated by proteolytic processing. Alphavirus replicase proteins are synthesized as a polyprotein, called P1234, which is cleaved into nsP1, nsP2, nsP3, and nsP4 by the carboxyl-terminal protease domain of nsP2. The cleavage intermediate P123؉nsP4 synthesizes minus-strand copies of the viral RNA genome, whereas the completely processed complex is required for plus-strand synthesis. To understand the mechanisms responsible for this sequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
113
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 87 publications
(122 citation statements)
references
References 39 publications
8
113
0
Order By: Relevance
“…They are initially synthesized in the form of a large nonstructural polyprotein (P1234) or two nonstructural polyproteins (P1234 and P123). These precursor molecules are subsequently cleaved in a highly regulated manner by the protease activity of nsP2 (7)(8)(9)(10). nsP1 possesses membrane-binding prop-NotI digestion.…”
Section: Hikungunya Virus (Chikv) Is a Mosquito-transmitted Oldmentioning
confidence: 99%
“…They are initially synthesized in the form of a large nonstructural polyprotein (P1234) or two nonstructural polyproteins (P1234 and P123). These precursor molecules are subsequently cleaved in a highly regulated manner by the protease activity of nsP2 (7)(8)(9)(10). nsP1 possesses membrane-binding prop-NotI digestion.…”
Section: Hikungunya Virus (Chikv) Is a Mosquito-transmitted Oldmentioning
confidence: 99%
“…2A and B). Notably, the nsP2 amino terminus has been previously proposed as a protease cofactor (27,28).…”
Section: For Details)mentioning
confidence: 99%
“…New mutants were made with the QuikChange XL site-directed mutagenesis kit (Stratagene). Polyprotein construct P12 CA 3 expressing a protease-defective mutant precursor from the T7 promoter has been described (49). Mutations R253E and W259A were cloned into the precursor in EcoRV-DraIII fragments.…”
Section: Methodsmentioning
confidence: 99%
“…To prevent the self-cleavage of the polyprotein, we used a protease active site mutant P12 CA 3 (49). Previous studies showed that P12 CA 3 targets differently from nsP1: the precursor was not found on the plasma membrane but instead resided in numerous punctuate structures in the cytoplasm, some of which were endo/ lysosomal vesicles (39).…”
Section: Vol 81 2007 Membrane Binding Mutants Of Sfv Nsp1 875mentioning
confidence: 99%
See 1 more Smart Citation